The Trypanosoma brucei RNA-binding protein DRBD18 ensures correct mRNA trans splicing and polyadenylation patterns - Bishola Tshitenge, Tania; Clayton, Christine (RNA, 2022)
The parasite Trypanosoma brucei grows as bloodstream forms in mammals, and as procyclic forms in tsetse flies. Transcription is polycistronic, all mRNAs are trans spliced, and polyadenylation sites are defined by downstream splicing signals. Expression regulation therefore depends heavily on post-transcriptional mechanisms. The RNA-binding protein DRBD18 was previously implicated in the export of some mRNAs from the nucleus in procyclic forms. It copurifies the outer ring of the nuclear pore, mRNA export factors and exon-junction-complex proteins. We show that for more than 200 mRNAs, DRBD18 depletion caused preferential accumulation of versions with shortened 3'-untranslated regions, arising from use of polyadenylation sites that were either undetectable or rarely seen in nondepleted cells. The shortened mRNAs were often, but not always, more abundant in depleted cells than the corresponding longer versions in normal cells. Their appearance was linked to the appearance of trans-spliced, polyadenylated RNAs containing only downstream 3'-untranslated region-derived sequences. Experiments with one mRNA suggested that nuclear retention alone, through depletion of MEX67, did not affect mRNA length, suggesting a specific effect of DRBD18 on processing. DRBD18-bound mRNAs were enriched in polypyrimidine tract motifs, and DRBD18 was found in both the nucleus and the cytoplasm. We therefore suggest that in the nucleus, DRBD18 might bind to polypyrimidine tracts in 3'-UTRs of mRNA precursors. Such binding might both prevent recognition of mRNA-internal polypyrimidine tracts by splicing factors, and promote export of the processed bound mRNAs to the cytosol.
Gesehen am 08.09.2023